Assembling Health Care Organizations Practice, Materiality and Institutions - Lindberg, Kajsa; Styhre, Alexander; Walter, Lars.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
Assembling Health Care Organizations combines an institutional theory perspective with a materialist view of the technologies, devices, biological specimens, and other material resources mobilized and put to work in health care work.
Keywords: Organization; International business enterpris; Management; Service industries; Behavioral economics; Industries; Organization; International Business; Management; Services; Behavioral/Experimental Economics; Industries